Contemporary methodology of teaching English punctuation: problems and new vistas - E. V. Mikhailovskaia; O. V. Sapunova (Вестник Самарского университета: История, педагогика, филология, 2021)
The article outlines the way the English system of punctuation marks is presented in contemporary ELT research and practice. The following types of sources are considered and analyzed in the article: grammar books for teaching English as the first, second or foreign language; reference books and web-sites aimed at preparing students for IELTS and TOEFL; books belonging to the genre known as popular science; purely scientific works on punctuation in general and the semicolon in particular. The main goals of the research are to reveal the central tendencies in teaching English punctuation on the example of the so-called weighty stops of vertical segmentation, namely the semicolon, and to see whether they manage to present a certain norm of using the stop. Thus, the present paper focuses on the semicolon one of the most controversial stops in the system, which has been proved to function both at the syntactic and stylistic levels. It is shown that a formal / grammatical approach is the most common way to treat punctuation in ELT literature; however, it does not take into account stylistic and prosodic peculiarities of the stops and thus fails to show the whole spectrum of its usage, as well as its phonetic and stylistic potential. Consequently, such an approach should not be applied to English one of the languages exhibiting a semantic-stylistic type of punctuation. It is proposed that the approach to be used in teaching English punctuation most effectively is pragmalinguistics, since it exploits a wide range of methods and means of analyzing a text, and also considers and highlights all the aspects of using the stops (their syntactic function, stylistic capacities and prosodic characteristics). Moreover, the article poses the question that the current methodology of the approach has to be further developed.